On the Limits of Automated Root Cause Analysis in Network Virtualization Scenarios using Language Models - Romero, Ana Beatriz L.; Carmo, Pedro R. X. do; Oliveira Filho, Assis T.; Kelner, Judith; Sadok, Djamel (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Root Cause Analysis (RCA) in networked and virtualized infrastructures is a complex task due to the volume of low-level metrics and the ambiguity of observable symptoms. Although Large Language Models (LLMs) have recently been explored for automated diagnosis, their effectiveness in realistic network scenarios remains unclear. This paper investigates the use of small-scale LLMs for network fault diagnosis through a systematic experimental study. We introduce the NetPerf-RCA Benchmark, composed of 24 representative network and virtualization scenarios, and evaluate multiple diagnostic approaches. Our results show that diagnostic effectiveness is primarily constrained by scenario characteristics and system observability.